HOME CARE FOR THE ELDERLY: : NURSE’S INTERVENTIONS - Freitas Nascimento, Riana; Pereira Fráguas, Diana (Health and Society, 2021)
The main objective of this study is to approach home care as an alternative of care provided in continuous care to the elderly by home nurses having the expertise or being a specialist in the field of gerontology. This is a qualitative review and exploratory scientific literature, conducted through online search of national and international articles, from 2009 to 2019. The study population was the elderly, who need nursing care in the home environment, instead of having care provided by visiting a medical clinic and being cared for at home under the supervision of their families. Thus, it is essential to identify that the nurse will be in order to contribute to the promotion and quality of life of these individuals in their family.